Time Free From Hospitalization in Children and Adolescents With Cystic Fibrosis: Findings From FEV1, Lung Clearance Index and Peak Work Rate - Gambazza, Simone; Mariani, Alessandra; Brivio, Anna; Carta, Federica; Blardone, Chiara; Lisiero, Saba; Russo, Maria; Colombo, Carla (Frontiers in Pediatrics, 2022)
Background An exercise test combined with a multiple breath washout nitrogen test (MBWN2) may offer a comprehensive clinical evaluation of cystic fibrosis (CF) disease in children with normal spirometry. The purpose of the present study is to explore whether information derived from spirometry, MBWN2, and exercise tests can help the CF multidisciplinary team to characterize time free from hospitalization due to pulmonary exacerbation (PE) in a cohort of pediatric patients with CF. Methods This prospective observational study was carried out at the Lombardia Region Reference Center for Cystic Fibrosis in Milano, Italy. In 2015, we consecutively enrolled children and adolescents aged <18 years with spirometry, MBWN2, and Godfrey exercise test performed during an outpatient visit. Results Over a median follow-up time of 2.2 years (interquartile range [IQR], 2.01; 3.18), 28 patients aged between 13.0 and 17.4 years were included. When lung functions were outside the normal range, 50% of patients were hospitalized 4 months after the outpatient visit, and their response to exercise was abnormal (100%). Half of the individuals with normal forced expiratory volume in the first second (FEV1) and abnormal lung clearance index (LCI) experienced the first hospital admission 9 months after the clinic visit, and 84.2% presented an abnormal response to exercise. Conversely, 15.8% had abnormal exercise responses when lung functions were considered normal, with half of the adolescents hospitalized at 11 months. Conclusion Maintaining ventilation homogeneity, along with a normal ability to sustain intense work, may have a positive impact on the burden of CF disease, here conceived as time free from hospitalization due to PE.